Bilateral cataract surgery with intraocular lens implant in a captive western lowland gorilla. Issue 5 (17th April 2017) - Warwick, Alasdair; Redrobe, Sharon; Lotery, Andrew; Watts, Jenny
Abstract: We report a case of bilateral cataract surgery performed in a 21‐year‐old western lowland gorilla. Phacoemulsification with intraocular lens insertion was performed using standard human surgical equipment. Visual function significantly improved. She subsequently mated and gave birth. Ultimately, cataract surgery enabled the birth of a baby gorilla.